The Impact of Communication Media on Islamic Education at the State Aliyah Madrasa in Banda Aceh City During the Covid 19 Pandemic - Hamdani Hamdani; Abdullah Abdullah; Rubino Rubino (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Communication is more successful when it is accurate and noise is reduced. As a result, all communication must be precise and devoid of interruption. Effective verbal and nonverbal communication is required for Islamic peace. Education is influenced by communication medium. Learning media and communication mediums are not the same. Media for learning and communication can overlap. The 2013 Curriculum improved educational media in classrooms. Learning is influenced by ICT. Learning media supplied via communication device Communication devices are used to transmit data. More information is required for this study.This research looks at how the media influences Islamic instruction at the State Aliyah Madrasa in Banda Aceh City. Throughout COVID-19.This qualitative study looks at how the media affected MAN Banda Aceh City during the COVID-19 pandemic. There were 19 informants. FGD, interviews, observation, and document studies were used in this study. Miles and Huberman were used to evaluate data in this investigation. The analysis of qualitative data organizes words into larger text.Field research, focus groups, and interviews led to the discovery of Google Classroom, Zoom, Meet, WhatsApp, Instagram, and Ruangguru.Some online learning programs are used at the Banda Aceh state Aliyah Madrasa. Only six prominent apps are frequently utilized. During internet interruptions, WhatsApp is used.Google meet, Zoom meeting, e-learning, and the Ruangguru app were the most frequently utilized tools to increase teacher-student communication at MAN Banda Aceh City during Covid 19. This online learning media platform disrupts the teacher-student relationship by adding value so that students feel accountable for good achievements. Students will be encouraged and supported to learn better if the teacher's communication with them is consistent, resulting in higher-quality learning results.